2020
DOI: 10.12688/f1000research.27098.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of possible biological control of Fusarium sp. using plant extracts and antagonistic species of microbes in vitro

Abstract: Background: Fusarium species is one of the most devastating fungi responsible for fruit and vegetable crops rot worldwide. The present study was designed to find an ecofriendly control measure for pathogenic Fusarium species, using suitable bioagents. Methods: Medicinal plant extracts were evaluated or their antifungal activities against Fusarium species using the poisoned food method. Antagonistic potency of some nonpathogenic microbes was also assessed on Fusarium species using the dual culture method. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Plant extracts are considered another alternative to traditional fungicides and pesticides as they produce bioagents that are effective against bacteria and fungi [ 20 ]. The volatile compounds and essential oils show promise as a substitute for antibacterial and antifungal agents in several studies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts are considered another alternative to traditional fungicides and pesticides as they produce bioagents that are effective against bacteria and fungi [ 20 ]. The volatile compounds and essential oils show promise as a substitute for antibacterial and antifungal agents in several studies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…From these disadvantages, antimicrobial characteristics have been sought in plants with intensified increase (Pushpavathi et al 2017). Since some plants have bioactive substances and are sources of resistance inducers El-sawy 2015;Zaker 2016;Hasan;Islam 2020), for the use of these active ingredients, several types of extraction can be used, such as aqueous, dry extract and oil extraction (Spadaro et al 2017).…”
Section: Natural Control Agentsmentioning
confidence: 99%
“…M. phaseolina is the chief cause of root rot disease in essential plants, such as, corn and cotton (Aly et al, 2007;Khaledi and Taheri, 2016). Fusarium is one destructive fungus that causes fruit and vegetable crop rot and is responsible for about 60-70% loss of fruit yield (Darmadi et al, 2019;Srinivas et al, 2019;Hasan et al, 2020). Ketta et al (2021) investigated the antagonism of R. leguminosarum combined with certain Trichoderma species against R. solani and F. solani, the primary sources of damping-off diseases in peas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other studies reported that Rhizobium isolates could inhibit the radial growth of F. oxysporum f. sp. ciceris and M. phaseolina in higher levels, as well as, improve each plant's growth and yield in vitro and the field (Arfaoui et al, 2006;Al-Ani et al, 2012;Hasan et al, 2020). The nifH is a well-known principal gene that encodes for one of the nitrogenase enzyme subunits (Rubio and Ludden, 2002).…”
Section: Introductionmentioning
confidence: 99%